Perception study of veterinary medicine students of the online modality to face-to-face - Flores Olivares, Carlos A.; Yañez Mariman, Pamela E.; Espinace López, Bárbara A.; Ortega Paiva, Lorena Andrea (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
SARS-CoV-2 in 2019, caused university students to start their online training process. In 2022, global restrictions gave way to a gradual return, where these students began their face-to-face training. Because of this, we surveyed 65 students to assess their perception of this transition. In relation to learning: 64.6% prefer face-to-face. Related to comfort, 61.5% prefer face-to-face. Related to improvement programs, 32.3% would carry out one online. In relation to dedication and commitment to their studies, 76.9% indicate that they were affected and 78.4% affirm that the virtual modality generated learning of digital tools.